THE ROLE OF TECHNOLOGY IN MODERN LANGUAGE EDUCATION (Лучшие интеллектуальные исследования, 2025)
Annotation: Technology plays a transformative role in modern language education by enhancing accessibility, engagement, and personalization in English Language Teaching. Digital tools and platforms such as AI-driven applications, virtual classrooms, and multimedia resources empower both learners and educators to achieve better outcomes. Institutions like Westminster College London demonstrate how integrating technology with pedagogy can support professional development and create more effective, learner-centered environments.